Analisis Dampak Penggunaan Teknologi Terhadap Lingkungan Sosial Mahasiswa Fakultas Ilmu Komputer - Pratiwi, Aris; Meytri, Devi Indra; Patriana, Orien (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2019)
Humans are social beings, because almost every day humans interact with other humans. This interaction raises tendency for communication media to be made directly or through communication devices. Seeing this, humans are increasingly skilled at creating a communicating such as gadget with the aim facilitating communication between humans. Gadget are communication tools that have many function. Where are the function has used different features. The gadget itself has become a necessity in communication in the era of the 21st century. The faculty of computer science, Sriwijaya University (Fasilkom Unsri) as a faculty engaged in information and communicatin technology in the world of technology that is not only a researcher as a user of the technology itself. This study using a qualitive descriptive method in which researcher attempt to describe the result of research using words or sentences in a logical structure, and explain the concept in relation to one another. A qualitive approach is also chosen because it can present the characteristics of the reaserch well, and the data obtained is more complete. This research was conducted to reveal the analys of the impact of using gadget technology on the social environment Inderalaya campus of Computer Science Faculty students from 2015 to 2018